Detection and quantification of microplastics from cultured green mussel Perna viridis in Bacoor Bay, Cavite, Philippines - Quennie Morales Bilugan; Jomel Saraza Limbago; Redel L. Gutierrez (Center for Science and Technology, IAIN Surakarta, 2021)
Microplastic contamination in the aquatic environment is a worldwide problem endangering aquatic organisms and human health. However, few reports were published in the Philippines especially in different edible fishery products. Hence, an investigation to report its prevalence in edible fishery products, especially in a fishery-dependent country, is necessary. This study was conducted to detect, characterize, and quantify microplastics from cultured Green mussel Perna viridis in Bacoor Bay, Cavite, Philippines. Samples (n=63) were collected from the inner, middle, and outer parts of Bacoor Bay. Isolation and characterization were conducted using wet peroxide oxidation-assisted density separation and stereomicroscopy, respectively. Results show a low concentration of microplastics from P. viridis cultured in Bacoor Bay. The highest microplastic count was observed from the inner bay (0.41 particle/gwet weight) followed by the middle bay (0.40 particle/gwet weight), then the outer bay (0.27 particle/gwet weight). The majority of microplastics in all sites were fibers (61%), color red (29%), and were dominated with > 10 to 50 Âµm length. This study revealed that microplastic is prevalent in Bacoor bay. Further study on confirming the microplastic polymers from P. viridis cultured in Bacoor bay is recommended.